Surface functionalized plasmonic sensors for uric acid detection with gold-graphene stacked nanocomposites - Onifade, Olabisi Abdullahi; Mohamad Azri, Dinie Dayana; Abu Bakar, Muhammad Hafiz; Alresheedi, Mohammed Thamer; Ng, Eng Khoon; Mahdi, Mohd Adzir; Muhammad Noor, Ahmad Shukri (Springer Verlag, 2024)
This study presented a surface-functionalized sensor probe using 3-aminopropyltriethoxysilane (APTES) self-assembled monolayers on a Kretschmann-configured plasmonic platform. The probe featured stacked nanocomposites of gold (via sputtering) and graphene quantum dots (GQD, via spin-coating) for highly sensitive and accurate uric acid (UA) detection within the physiological ranges. Characterization encompassed the field emission scanning electron microscopy for detailed imaging, energy-dispersive X-ray spectroscopy for elemental analysis, and Fourier transform infrared spectroscopy for molecular identification. Surface functionalization increased sensor sensitivity by 60.64%, achieving 0.0221 °/(mg/dL) for the gold-GQD probe and 0.035 5 °/(mg/dL) for the gold-APTES-GQD probe, with linear correlation coefficients of 0.8249 and 0.8509, respectively. The highest sensitivity was 0.070 6 °/(mg/dL), with a linear correlation coefficient of 0.993 and a low limit of detection of 0.2 mg/dL. Furthermore, binding affinity increased dramatically, with the Langmuir constants of 14.29 µM−1 for the gold-GQD probe and 0.000 1 µM−1 for the gold-APTES-GQD probe, representing a 142 900-fold increase. The probe demonstrated notable reproducibility and repeatability with relative standard deviations of 0.166% and 0.013%, respectively, and exceptional temporal stability of 99.66%. These findings represented a transformative leap in plasmonic UA sensors, characterized by enhanced precision, reliability, sensitivity, and increased surface binding capacity, synergistically fostering unprecedented practicality.